Five factor model traits as a predictor of suicide ideation and interpersonal suicide risk in a college sample - DeShong, Hilary L.; Tucker, Raymond P.; O’Keefe, Victoria M.; Mullins-Sweatt, Stephanie N.; Wingate, LaRicka R. (Psychiatry research, 2015)
Research has demonstrated an inconsistent relationship between suicide ideation and personality traits. This is the first study to empirically examine the relationship of the Five Factor Model of personality with current, past and no suicide ideation, and with the two interpersonal risk factors of suicide: thwarted belongingness and perceived burdensomeness (Joiner, T., 2005. Why people die by suicide. Cambridge, MA, US: Harvard University Press). Results indicate that high neuroticism was associated with both current ideation and a history of suicide ideation and extraversion was associated with current ideation. Neuroticism was positively related to thwarted belongingness and perceived burdensomeness, while extraversion was negatively related to these interpersonal predictors of suicide. Agreeableness was negatively related to thwarted belongingness but not perceived burdensomeness, indicating differentiated patterns of relationships between this personality domain and the two suicide constructs. Furthermore, these personality domains predicted 23.82% of variance for thwarted belongingness and 15.07% of the variance for perceived burdensomeness, above and beyond demographic variables associated with suicide ideation. This study, which was conducted with a college sample, demonstrates the potential benefit of identifying predispositional risk factors for suicide ideation and interpersonal predictors of suicide. This may have implications for the development of upstream preventative measures against suicide. •Low extraversion and high neuroticism were positively related to suicide ideation.•Neuroticism positively predicted perceived burdensomeness and thwarted belongingness.•Extraversion and agreeableness negatively predicted thwarted belongingness.